A survey on Islamic economics and finance literatures indexed by Scopus Q1 via thematic analysis approach - Laila, Nisful; Slamet Rusydiana, Aam; Che Mohd Salleh, Marhanum; Sukmaningrum, Puji Sucia (Primrose Hall Publishing Group, 2020)
The purpose of this study is to review recent research on Islamic economics and finance published in reputable journals indexed by Scopus Q1. Thematic analysis is adopted to find similarities among 177 selected literatures on Islamic economics and finance, published from year 2014 to 2018. Results of analyses show that at least 20 Q1 Scopus journals have published researches on Islamic economics and finance and most of the research was published at Pacific-Basin Finance Journal, Journal of Economic Behaviour & Organisation, Journal of International Financial Market, Institution & Money and Journal of Business Ethics. Overall, 84 percent of the researches were done quantitatively. Based on the findings, it is observed that there is a bright future of articles’ publication at this domain and future researchers should focus more on quality findings on emerging areas including Takaful, Islamic microfinance, Islamic crowdfunding, waqf, and other areas that have received high concentration by industry players as well as the public at large. This research is able to provide information on important topics that need to be researched in subsequent studies. The increase of research in Islamic economics and finance can be a solution to the literacy limitations at this time.